Mesozoic tectonic evolution of the south Orkney microcontinent, Scotia arc, Antarctica - Trouw, RAJ; Passchier, C. W.; Simoes, LSA; Andreis, R. R.; Valeriano, C. M. (Cambridge University Press, 1997)
The South Orkney Islands are the exposed part of a continental fragment on the southern limb of the Scotia are. The islands are to a large extent composed of metapelites and metagreywackes of probable Triassic sedimentary age. Deformation related to an accretionary wedge setting, with associated metamorphism from anchizone to the greenschist facies, are of Jurassic age (176-200 Ma). on Powell Island, in the centre of the archipelago, five phases of deformation are recognized. The first three, associated with the main metamorphism, are tentatively correlated with early Jurassic subduction along the Pacific margin of Gondwana. D-4 is a phase of middle to late Jurassic crustal extension associated with uplift. This extension phase may be related to opening of the Rocas Verdes basin in southern Chile, associated with the breakup of Gondwanaland. Upper Jurassic conglomerates cover the metamorphic rocks unconformably. D-5 is a phase of brittle extensional faulting probably associated with Cenozoic opening of the Powell basin west of the archipelago, and with development of the Scotia are.